Anuncios macroeconómicos y mercados Accionarios: El caso Latinoamericano (2011)
Do stock markets reflect changes on the macroeconomic fundamentals? . The semi-strong form of the Efficient market hypothesis (HEM - Fama 1970) asserts that stock prices should react immediately to the surprise content on announcements of macroeconomic variables, without predictable over or under reaction. We test this in the six main Latin-American equity markets: Argentina, Brazil, Chile, Colombia, México and Perú, for the announcements of Consumer Price Inflation, Central Bank interest rate, GDP growth, Trade Balance and Unemployment rate. Following Flannery and Protopapadakis (2002), we estimate the effect of the surprises of such announcements, using time series models of conditional volatility, controlling of the exchange rate and international stock markets. We found that the effects on the market returns are significant and with the expected sign only for the CPI in Mexico, for the interest rate in Chile and Colombia, and for Unemployment on those three markets. Moreover, in some cases the stock markets incorporate the announcement with a lag, whereas in others, they react to the announcement rather than to the surprise, in conflict with the HEM. We conclude that the Latin-American stock markets react only partially to the macroeconomic announcements and not fully incorporating the new information in an efficient manner.